Analysis of work motivation of room division employees and service quality room on guest satisfaction - Sihombing, Daniel; Tambunan, Sontina Griche; Sinay, Kaleb Yusuf (Institute of Computer Science (IOCS), 2025)
Research analyzes the influence of work motivation and service quality on guest satisfaction at the Palapa Hotel, Tarutung, North Tapanuli Regency. A quantitative approach was used with a survey method through questionnaires distributed to 80 respondents consisting of hotel guests and room division employees. The variables analyzed are work motivation (X1), service quality (X2), and guest satisfaction (Y). Multiple linear regression tests, t tests, and F tests are used to measure the influence between these variables. The research results show that both work motivation (X1) and service quality (X2) have a significant influence on guest satisfaction partially and simultaneously. The t test shows that each independent variable has a significant effect with a calculated t-value that is greater than the t-table. Apart from that, the F test carried out shows that the F-test value is greater than the F-table (129,868 > 3,115) with a significance level of 0.000, which means that simultaneously the variables of work motivation and service quality have a significant influence on guest satisfaction. The coefficient of determination (R²) value of 65.8% indicates that work motivation and service quality variables jointly influence guest satisfaction, while 34.2% is influenced by other factors not studied. The conclusion of this research is that Palapa Hotel needs to continue to improve employee work motivation and service quality to maintain and increase guest satisfaction. By paying attention to motivation and service aspects, it is hoped that hotels can provide a more positive and memorable experience to guests, which will ultimately support the sustainability of the hotel's business in facing competition in the hotel industry.